Analysis of Ghrelin and Asymmetric Dimethylarginine (ADMA) as Endothelial Dysfunction Marker Among Obese Men - Lia Meliani; Mansyur Arif; Indriyanti Rafi Sukmawati (The Indonesian Biomedical Journal, 2012)
BACKGROUND: Ghrelin has many biological activities such as regulating energy homeostasis and recent studies have shown its effects in the cardiovascular system. Ghrelin concentration decreases in obese man that indicates relatioship between ghrelin and energy homeostasis. Ghrelin also improves endothelial function by increasing the bioavaibility of nitric oxide (NO). The bioavaibility of NO is also influenced by ADMA. ADMA is an endogenous competitive inhibitor of endothelial nitric oxide synthase (eNOS), which is significantly elevated during endothelial dysfuction. This study aimed to evaluate the relationship of ADMA and ghrelin with central obesity based on waist circumference and to evaluate the relationship of total ghrelin and ADMA in centrally obese men. METHODS: Total ghrelin and ADMA were measured in 20 non-obese men (waist circumference (WC) 78.85±4.40 cm) and 60 centrally obese men (WC 97.54±5.94 cm). Anthropometric measurements (height, weight, BM, waist circumference and blood pressure) were also recorded. Statistic were carried out by the Spearman and Pearson bivariate correlation analysis and independent sample T test. RESULTS: ADMA concentrations were significantly higher in centrally obese men than in normal weight controls (p-value <0.05), whereas total ghrelin concentrations were not significantly lower in centrally obese men than in normal weight controls (p-value >0.05). Ghrelin total concentrations were significantly lower in centrally obese men with metabolic syndrome than in normal weight controls (p-value <0.05). No significant correlation existed between total ghrelin and ADMA.CONCLUSIONS: No correlation existed between ADMA and total ghrelin. The pathway of ghrelin in altering vascular function may not involve ADMA.KEYWORDS: ghrelin, ADMA, endothelial dysfunction, obese